Developing a Record Archiving System in Eastern Visayas State University – Burauen Campus - Elpidio Cabitlada Villarosa (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Records archiving, and storage pose a strategic role in managing the university system efficiently and effectively. It also documents the planning and implementation of certain services, allowing proper tracking of work. In this study, the researcher developed a record archiving system for Eastern Visayas State University Burauen Campus. The system is able to provide a paperless records management system, deliver an easier pace for retrieving and recording data, and secure a reliable database backup. The researcher utilized a system developmental research approach that consists of two phases, the analysis phase where the needs are being assessed and the design and development phase of the record archiving system.